2015
DOI: 10.1186/s12889-015-1467-1
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic disease risk and HIV status in rural South Africa: establishing a baseline

Abstract: BackgroundTo inform health care and training, resource and research priorities, it is essential to establish how non-communicable disease risk factors vary by HIV-status in high HIV burden areas; and whether long-term anti-retroviral therapy (ART) plays a modifying role.MethodsAs part of a cohort initiation, we conducted a baseline HIV/cardiometabolic risk factor survey in 2010–2011 using an age-sex stratified random sample of ages 15+ in rural South Africa. We modelled cardiometabolic risk factors and their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
78
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 21 publications
8
78
0
Order By: Relevance
“…Our findings are broadly consistent with earlier reports, including a study among black African women in rural South Africa and a meta-analysis of clinical trials in European-descent populations [31,32]. These studies suggested that first-line ART is associated with raised cholesterol and TG [31,32].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are broadly consistent with earlier reports, including a study among black African women in rural South Africa and a meta-analysis of clinical trials in European-descent populations [31,32]. These studies suggested that first-line ART is associated with raised cholesterol and TG [31,32].…”
Section: Discussionsupporting
confidence: 92%
“…These studies suggested that first-line ART is associated with raised cholesterol and TG [31,32]. In addition, a study of metabolic complications in a European-descent population found that the use of combined NNRTI and PI was associated with a fivefold higher prevalence of hypertriglyceridaemia [33].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in this rural population have reported higher BMIs in females, with an age-adjusted prevalence of obesity of 26% in females aged 15 and older compared to 7% in similarly aged males [17] and a 24.6% higher prevalence of obesity in females in those over 50 years [18]. Similar differences were evident in rural Ghana where the prevalence of obesity in women was seven times that in men [24].…”
Section: Discussionsupporting
confidence: 66%
“…Individuals who had previously participated in earlier studies investigating the interaction between HIV and NCDs [17,18] were invited to participate and, to supplement this group, a random sample of individuals aged 40–60 years was drawn from the 2013 Agincourt HDSS database. The sample was stratified by sex to achieve equal numbers of males and females.…”
Section: Methodsmentioning
confidence: 99%
“…Some of these individuals had participated in earlier studies, and their participation here allowed for longitudinal analysis of CMD risk factors [35,36]. The questionnaire administered to participants only included questions not already included in the HAALSI study.…”
Section: Methodsmentioning
confidence: 99%